In Vitro Effects of Different Surface Preparation Techniques on Shear Bond Strength of Direct to Indirect Composite Resin - Kaviani, Azita; Gharizadeh, Naghmeh; Alinejad, Hengameh; Moosavi, Reyhaneh (Journal of Dental School, 2019)
Objective: Repair of an indirect restoration is usually preferred over its replacement. This study aimed to evaluate the effect of silane in different surface preparation techniques on the bond strength of direct to indirect composite resin. Methods: For this in vitro experimental study, 48 indirect composite cubes were fabricated, divided into 4 groups of 12 and subjected to the following preparation techniques: Group 1. Sandblasting with 50μaluminum oxide particles (SB), Group 2. Sandblasting+ silanization (SB+Sil), Group 3. Etching with 9.5% hydrofluoric (HF) acid, Group 4. Etching with 9.5% HF acid+ silanization (HF+Sil). Before the restoration process, specimens were subjected to 500 thermal cycles and received surface preparations. Single Bond adhesive was applied to the surface in all groups. Specimens were restored with direct composite resin and stored in an incubator at 37°C for 24h. Fracture was induced in the specimens by an Instron machine and the shear bond strength was measured. Data were converted to mega Pascal and analyzed using two-way ANOVA and Tukey’s post hoc. Results: The highest shear bond strength was 13.85 (2.75) MPa and belonged to group 1; while the lowest bond strength was 8.43 (1.35) MPa and observed in group 2. Conclusion: Based on the obtained results, composite surface preparation by sandblasting yields more favorable results than HF acid etching and application of silane can also increase the bond strength.